Positionally cloned asthma susceptibility gene polymorphisms and disease risk in the British 1958 Birth Cohort. Issue 5 (22nd February 2009) - Blakey, J D; Sayers, I; Ring, S M; Strachan, D P; Hall, I P
Abstract : Objective: The aim of this study was to estimate the contribution of polymorphisms in the positionally cloned asthma candidate genes ADAM33, PHF11, DPP10, GPRA and PTGDR to the risk of asthma, total and specific immunoglobulin E level, lung function and wheezing in a large, nationally representative, population. Methods: An association analysis was undertaken using genotype data for tagging and previously associated single nucleotide polymorphisms (SNPs) in regions of these genes and longitudinal phenotype data from singletons of white ethnicity in the British 1958 Birth Cohort DNA archive (n = 7703). Population-attributable risk fractions for SNPs showing association were calculated. Results: Polymorphisms producing small but statistically significant increases in asthma risk (OR 1.1 per allele) were identified in DPP10 and ADAM33, with the strongest evidence being for SNPs tagging the DPP10 gene. No individual SNP in any gene under study markedly increased risk for any of the phenotypes in the population studied. Conclusions: These data suggest that DPP10 and ADAM33 influence asthma risk in the UK population. However, the effects driven by any given locus are small, and genotyping of multiple polymorphisms in many genes will be needed to define a full genetic profile for disease risk.